Digital Activism of Wahana Lingkungn Hidup Indonesia (Walhi) Hashtag in Voicing Environmental Issues on Social Media - Indainanto, Yofiendi Indah; Fatharani, Rachela Belinda; Halim, Rizki; Mulyono, Deony Dewanggi (East Asian Journal of Multidisciplinary Research, 2024)
The purpose of the research is to understand the impact of digital campaign strategies on changing people's behaviour and actions towards environmental protection. This research method uses a qualitative study by looking at social media posts on @walhi.national. The findings show that Walhi has played an important role in promoting the environmental awareness movement in Indonesia. The dominant themes include the criminalisation of environmental activists, opposition to mining and land reclamation projects, and forest conservation. Through the use of hashtags, Walhi has been very effective in raising awareness of environmental issues. However, the extensive use of hashtags reduces the connectivity between content. The strategies used by Walhi, the use of relevant hashtags, strong narratives and collaboration between central and regional Walhi are considered capable of building an environmental movement. Strengthening the environmental movement and raising public awareness are Walhi's strategies for mobilising support.